High-refractive-index dual-curing adhesive as well as preparation method and application thereof

By using high-fold double curing glue technology in optical glue, the combination of epoxy resin, reactive acrylate and inorganic filler, combined with UV and thermal curing, the insufficient performance of optical glue in high temperature and high humidity environments is solved, and high bond strength, weather resistance and optical performance are improved.

CN119505716APending Publication Date: 2025-02-25WUHAN SUNSHINE OPTOELECTRONICS TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411538680.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing optical glue lacks performance in high temperature and high humidity environments, and is prone to bubble problems and poor visual effects.

Method used

High-fold double curing glue is used to combine epoxy resin, acrylates containing reactive groups and inorganic fillers, combined with UV curing and thermal curing technology to achieve dual curing, thereby improving bonding strength and high temperature resistance.

Benefits of technology

Good bonding strength, weather resistance and optical properties in high temperature and high humidity environments are achieved, avoiding bubble problems and poor visual effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112240690000141
    Figure BDA0005112240690000141
  • Figure BDA0005112240690000151
    Figure BDA0005112240690000151
Patent Text Reader

Abstract

The invention belongs to the technical field of optical adhesives, and particularly relates to a high-refractive-index dual-curing adhesive as well as a preparation method and application thereof. The high-refractive-index dual-curing adhesive comprises a component A, a component B and a component C, wherein the component A comprises 40-80 parts of epoxy resin, 10-40 parts of first acrylic ester and 15-30 parts of first inorganic filler; the component B is prepared from 20 to 50 parts of second acrylic ester, 30 to 80 parts of second inorganic filler and 5 to 20 parts of curing agent; wherein the first acrylate at least comprises a (methyl) acrylate monomer containing one or more reactive groups, and the reactive groups are selected from hydroxyl, epoxy or carboxyl; the second acrylic ester is selected from any one or a combination of more of a (methyl) acrylic acid aryl ester monomer, a (methyl) acrylic acid alkyl ester monomer or a (methyl) acrylic acid alkyl ether ester monomer. The curing adhesive is a high-refractive-index optical adhesive which is stable in system and excellent in performance after being cured to form a film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical adhesives, and in particular relates to a high-refractive dual-curing adhesive and a preparation method and application thereof. Background Art

[0002] Optical glue is a special adhesive used to bond transparent optical components (such as lenses, etc.). It is colorless and transparent, has a light transmittance of more than 90%, has good bonding strength, can be cured at room temperature or medium temperature, and has small curing shrinkage.

[0003] Optical adhesives can be divided into acrylic optical adhesives, epoxy optical adhesives, polyurethane optical adhesives and silicone optical adhesives according to the category of the main resin. Optical adhesives with different main resins have different performance characteristics. Generally, epoxy optical adhesives have higher bonding strength, but poor aging resistance and are prone to yellowing. Polyurethane optical adhesives have better impact resistance and aging resistance, but their moisture resistance is obviously insufficient. Silicone resin has an advantage of extremely excellent weather resistance, but poor bonding strength. Acrylic optical adhesives are between various systems and have higher optical properties, which are particularly suitable for bonding optical devices. Although acrylic optical adhesives have better comprehensive properties, they also have insufficient high temperature and high humidity resistance, and are prone to bubble problems, thereby producing bright spots. On the other hand, during the use of acrylic optical adhesives, there are currently widespread problems such as decreased screen brightness and contrast, and poor visual effects. Therefore, the present invention proposes a high-fold dual-curing adhesive with good bonding strength, high temperature resistance, weather resistance and optical properties to solve this problem. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the present invention provides a high-flex dual-curing adhesive and a preparation method and application thereof.

[0005] The technical solution provided by the present invention is as follows:

[0006] A high-fold dual-curing adhesive comprises the following components in parts by weight:

[0007] Component A comprises: 40-80 parts of epoxy resin, 10-40 parts of first acrylate, and 15-30 parts of first inorganic filler;

[0008] and component B, which includes: 20-50 parts of a second acrylate, 30-80 parts of a second inorganic filler, and 5-20 parts of a curing agent;

[0009] in:

[0010] The first acrylate comprises at least a (meth)acrylate monomer containing one or more reactive groups, wherein the reactive groups are selected from hydroxyl, epoxy or carboxyl groups;

[0011] The second acrylic acid ester is selected from any one or more combinations of (meth)acrylic acid aryl ester monomers, (meth)acrylic acid alkyl ester monomers or (meth)acrylic acid alkyl ether ester monomers.

[0012] In the above technical solution:

[0013] The curing agent is set in the B component. By separating the A component from the B component, the room temperature curing reaction of the epoxy resin can be avoided, so that the high-fold dual-curing adhesive has good fluidity and is easy to use in construction;

[0014] Since the first acrylate has both an unsaturated double bond that can react with the second acrylate and a reactive group that can react with the epoxy resin, the epoxy group can be thermally cured with the reactive group, and the double bonds can be photocured, thereby achieving dual curing. Therefore, when components A and B are mixed and used, various resins are cross-linked with each other under the action of thermal curing agents and ultraviolet curing agents, thereby improving the bonding strength and high temperature resistance between the cured adhesive layer and the substrate or glass plate.

[0015] Specific:

[0016] The type of the first acrylate is any one or a combination of two of a (meth)acrylate aryl ester monomer, a (meth)acrylate alkyl ester monomer or a (meth)acrylate alkyl ether ester monomer, and the first acrylate includes at least a (meth)acrylate monomer containing one or more reactive groups, wherein the reactive groups are selected from hydroxyl, epoxy or carboxyl groups;

[0017] The type of the second acrylic acid ester is any one or more combinations of (meth)acrylic acid aryl ester monomers, (meth)acrylic acid alkyl ester monomers or (meth)acrylic acid alkyl ether ester monomers;

[0018] The first acrylate may be selected to be the same type or different from the second acrylate.

[0019] The epoxy resin in component A is an epoxy resin with an alicyclic or aromatic backbone and two or more glycidyl ether groups, glycidyl esters or dehydrated glyceryl esters.

[0020] Preferably, the epoxy resin is selected from any one or more combinations of bisphenol A epoxy resin, bisphenol S epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, novolac epoxy resin, and epoxy glycidyl ester.

[0021] Specifically, the bisphenol A epoxy resin includes one or more of E-44 epoxy resin, E-51 epoxy resin, E-32 epoxy resin, E-35 epoxy resin, E-54 epoxy resin, E128 epoxy resin, E20 epoxy resin, and E10 epoxy resin.

[0022] Specifically, the bisphenol F type epoxy resin includes one or more of epoxy resin DER354, epoxy resin DER354LV, EXA-830CRP, epoxy resin 828EL, 862, YDF170, and YDF175.

[0023] Specifically, the bisphenol S epoxy resin includes one or more of S33 bisphenol S epoxy resin, 185S bisphenol S epoxy resin, and 300SS bisphenol S epoxy resin.

[0024] The above-mentioned bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin are only examples. Similarly, the biphenyl epoxy resin, novolac epoxy resin, and epoxy glycidyl ester described in this application can all be selected from commercially available models.

[0025] Preferably, when the first acrylate includes at least a (meth)acrylate alkyl ester monomer containing one or more epoxy groups, the (meth)acrylate monomer is an acrylate monomer having an alkyl group, an alkyl ether group, or an aromatic group having 1-2 benzene ring groups as a skeleton and having one or more glycidyl ether groups or epoxy cyclohexyl groups at the end.

[0026] Furthermore, the (meth)acrylic acid monomer chain segment containing one or more epoxy groups contains C 1 -C 20 Alkyl, C 3 -C 20 Heterocycloalkyl, C 1 -C 20 Alkyl, C 6 -C 30 Any one or more combinations of aromatic groups.

[0027] Preferably, the second acrylate comprises at least a (meth)acrylate aryl ester containing two or more substituted or unsubstituted phenyl groups.

[0028] More preferably, the second acrylate contains the following two phenyl groups: two phenyl groups connected by any one of a single bond, a C1-C5 alkyl group, an ether bond, and a condensed bond, such as naphthalene, anthracene, biphenyl, diphenylmethane, diphenyl ether, bisphenol A, and the like.

[0029] Preferably, the inorganic filler is selected from one or more combinations of organically modified or unmodified metal oxides and silicon dioxide. The average particle size of the inorganic filler in the technical solution of the present application is 10-50 nm. Examples of metal oxides include, but are not limited to, metal oxides composed of one or two metal elements of zirconium, titanium, germanium, niobium, zinc, hafnium, tantalum, bismuth, molybdenum, tin, indium, antimony, cerium, neodymium, hafnium, and tantalum with high refractive index, and specific examples include: zirconium dioxide, titanium dioxide, etc. Particle size 10-50 nm.

[0030] Organic modification is a well-known and commonly used technical means such as conventional silane coupling agent modification. The organic modified zirconium dioxide and the like specifically selected in this application are commercially available.

[0031] Preferably, the curing agent includes a light curing agent and a heat curing agent.

[0032] Furthermore, the photocuring agent may be a photoinitiator conventionally used in photocurable resin compositions, such as benzoin photoinitiators, ketone photoinitiators, phosphine oxide photoinitiators, peroxide photoinitiators, and oxime ester photoinitiators.

[0033] Furthermore, the thermal curing agent may be a thermal curing initiator conventionally used for thermal curing resin compositions, such as an amine-based curing agent, an acid anhydride-based thermal curing agent, an imidazole-based thermal curing agent, an acid anhydride-based curing agent, and the like.

[0034] Amine curing agents include, for example, N,N-dimethylbenzylamine, triethylenetetramine, diethyltoluenediamine, 1,3-cyclohexanedimethylamine, dapsone, isophoronediamine, 4,4'-bis-sec-butylaminodiphenylmethane, ammonium-blocked Lewis acid salts, and the like.

[0035] In the present application, the thermal curing agent preferably contains an amine curing agent. Based on this scheme, the epoxy groups in the epoxy resin and acrylate react with the thermal curing agent amine to form a large number of hydroxyl groups, which form hydrogen bonds with the hydroxyl groups on the surface of the glass substrate. In addition, the epoxy groups can react with the hydroxyl groups on the glass substrate to form chemical bonds, which can firmly connect the glass substrate and the resin and improve the bonding strength of the interface.

[0036] Preferably, the technical solution of the present application further comprises a silane coupling agent, wherein the silane coupling agent contains at least one functional group of hydroxyl, epoxy or amino, wherein the hydroxyl, epoxy or amino functional group can be located on any carbon of the silane coupling agent.

[0037] In parts by weight, in the present application, the amount of silane coupling agent added is 1-10 parts by weight.

[0038] Based on this scheme, the silane coupling agent contains silicon-oxygen-carbon bonds, which can react with the hydroxyl groups on the surface of the glass substrate to form silicon-oxygen-carbon chemical bonds after hydrolysis, so that the silane molecules can be firmly connected to the surface of the glass substrate. The epoxy group and acryl group at the other end can react with the epoxy group and acryl group in the resin, thereby being firmly connected to the resin, thereby improving the adhesion between the resin and the glass substrate.

[0039] In the present application, the silane coupling agent is specifically selected as: a silane coupling agent having a hydroxyl group, an epoxy group or an amino group at one end and a siloxane group at the other end. Examples include but are not limited to: 3-aminopropyl diisopropylethoxysilane, y-aminopropyl triethoxysilane, N-(β-aminoethyl)-y-aminopropyl trimethyl (ethyl)oxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl triethoxysilane, 3-glycidyloxypropyl methyl diethoxysilane, etc.

[0040] Furthermore, functional additives may be added to the solution, including dispersants, solubilizers, surfactants, leveling agents, defoamers, adhesion promoters, etc.

[0041] In the embodiment of the present invention, a surfactant is added, and the specific options include but are not limited to: polyether-modified polydimethylsiloxane, polyester-modified polydimethylsiloxane containing multiple acrylate functional groups, hydroxyl-containing polyether-modified polydimethylsiloxane, and acryloxy-modified silane polymer.

[0042] In a second aspect, the present application provides a method for preparing a high-fold dual-curing adhesive, comprising the following steps:

[0043] S1: adding epoxy resin, first acrylate and first inorganic filler into a reaction kettle and stirring to obtain component A;

[0044] S2: adding the second acrylate, the second inorganic filler and the curing agent into a reaction kettle and stirring to obtain component B;

[0045] S3: Add component A and component B into a reaction kettle at a weight ratio of (1-1.5):1 and stir to obtain a composition.

[0046] In a third aspect, the present application provides an application of a high-flex dual-curing adhesive, in which a composition obtained by mixing component A and component B at room temperature is pre-cured under ultraviolet light, and then cured at a temperature of 100-130°C to obtain an adhesive layer.

[0047] The technical solution of the present application is also applicable to a curing method in which UV and thermal curing are performed simultaneously, or thermal curing is performed first and then UV curing.

[0048] In the present application, the epoxy resin monomer in component A, the first acrylate with reactive groups, and the second acrylate in component B will form a polymerized whole with strong chemical bonds after curing, thereby improving the thermal stability and mechanical strength of the material. After the epoxy resin and acrylate are mixed, they have good fluidity. UV curing is first used. The reactive epoxy groups in the components first undergo a ring-opening reaction to promote the cross-linking reaction with the acrylate. After the thermal curing reaction is complete, the adhesive layer has a dense cross-linking density and has good water and oxygen barrier, high temperature resistance and other properties. DETAILED DESCRIPTION

[0049] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0050] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially. Unless otherwise specified, the test methods used in the examples of the invention are all conventional methods.

[0051] Embodiment 1:

[0052] S1: 60 parts by weight of 4,5-epoxytetrahydrophthalic acid diglycidyl ester, 25 parts by weight of 2-hydroxyethyl methacrylate, 15 parts by weight of 4-biphenylmethanol acrylate, 20 parts by weight of organically modified zirconium dioxide and 2 parts by weight of 3-glycidyloxypropyltrimethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component A.

[0053] S2: 40 parts by weight of 4-biphenylmethanol acrylate, 40 parts by weight of organically modified zirconium dioxide, 5 parts by weight of isophoronediamine, 5 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 8 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0054] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0055] Embodiment 2:

[0056] S1: 60 parts by weight of 4,5-epoxytetrahydrophthalic acid diglycidyl ester, 25 parts by weight of glycidyl methacrylate, 15 parts by weight of 4-biphenylmethanol acrylate, 20 parts by weight of organically modified zirconium dioxide and 2 parts by weight of 3-glycidyloxypropyltrimethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component A.

[0057] S2: 40 parts by weight of 4-biphenylmethanol acrylate, 40 parts by weight of organically modified zirconium dioxide, 5 parts by weight of isophoronediamine, 5 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 8 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0058] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0059] Embodiment 3:

[0060] S1: 60 parts by weight of 4,5-epoxytetrahydrophthalic acid diglycidyl ester, 25 parts by weight of 3,4-epoxycyclohexyl methacrylate, 15 parts by weight of 4-biphenylmethanol acrylate, 20 parts by weight of organically modified zirconium dioxide and 2 parts by weight of 3-glycidyloxypropyltrimethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500rpm, and the stirring time is 4h to obtain component A.

[0061] S2: 40 parts by weight of 4-biphenylmethanol acrylate, 40 parts by weight of organically modified zirconium dioxide, 5 parts by weight of isophoronediamine, 5 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 8 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0062] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0063] Embodiment 4:

[0064] S1: 55 parts by weight of bisphenol A epoxy diacrylate, 35 parts by weight of 2-hydroxyethyl methacrylate, 15 parts by weight of organically modified titanium dioxide and 1 part by weight of y-aminopropyltriethoxysilane were added into a reaction kettle and stirred. The temperature was controlled at about 40° C., the stirring speed was 1500 rpm, and the stirring time was 4 hours to obtain component A.

[0065] S2: 35 parts by weight of 3-phenoxybenzyl acrylate, 45 parts by weight of organically modified titanium dioxide, 8 parts by weight of isophoronediamine, 3.5 parts by weight of diphenyl (2,4,6-triformyl) phosphine oxide and 3 parts by weight of polyether modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0066] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0067] Embodiment 5:

[0068] S1: 55 parts by weight of bisphenol A difunctional epoxy acrylate, 35 parts by weight of 2-hydroxyethyl methacrylate, 15 parts by weight of organically modified titanium dioxide and 1 part by weight of y-aminopropyltriethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component A.

[0069] S2: 35 parts by weight of isobutyl acrylate, 45 parts by weight of organically modified titanium dioxide, 8 parts by weight of isophorone diamine, 3.5 parts by weight of diphenyl (2,4,6-triformyl) phosphine oxide and 3 parts by weight of polyether modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0070] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0071] Embodiment 6:

[0072] S1: 58 parts by weight of bisphenol F diglycidyl ether, 22 parts by weight of 1,2-phthalic acid-1-[2-[(2-methyl-1-oxo-2-propen-1-yl)oxy]ethyl]-2-(2-oxiranylmethyl) ester (CAS: 57043-36-4), 15 parts by weight of 3-phenoxybenzyl acrylate, 15 parts by weight of organically modified titanium dioxide and 1 part by weight of y-aminopropyltriethoxysilane were put into a reaction kettle and stirred. The temperature was controlled at about 40° C., the stirring speed was 1500 rpm, and the stirring time was 4 hours to obtain component A.

[0073] S2: 35 parts by weight of 4-biphenylmethanol acrylate, 45 parts by weight of organically modified titanium dioxide, 8 parts by weight of isophoronediamine, 3.5 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 3 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0074] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0075] Embodiment 7:

[0076] S1: 40 parts by weight of bis(7-oxabicyclo[4.1.0]3-heptylmethyl)adipate, 30 parts by weight of glycidyl methacrylate, 25 parts by weight of organically modified zirconium dioxide and 1 part by weight of y-aminopropyltriethoxysilane were put into a reaction kettle and stirred. The temperature was controlled at about 40°C, the stirring speed was 1500 rpm, and the stirring time was 4 hours to obtain component A.

[0077] S2: 25 parts by weight of bisetherfluorene acrylate, 35 parts by weight of organically modified zirconium dioxide, 12 parts by weight of isophoronediamine, 2 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 5 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0078] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0079] Embodiment 8:

[0080] S1: 40 parts by weight of bis(7-oxabicyclo[4.1.0]3-heptylmethyl)adipate, 30 parts by weight of glycidyl methacrylate, 25 parts by weight of organically modified zirconium dioxide and 1 part by weight of y-aminopropyltriethoxysilane were put into a reaction kettle and stirred. The temperature was controlled at about 40°C, the stirring speed was 1500 rpm, and the stirring time was 4 hours to obtain component A.

[0081] S2: 25 parts by weight of 1,6-hexanediol diacrylate, 35 parts by weight of organically modified zirconium dioxide, 12 parts by weight of isophorone diamine, 2 parts by weight of diphenyl (2,4,6-triformyl) phosphine oxide and 5 parts by weight of polyether modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0082] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0083] Embodiment 9:

[0084] S1: 60 parts by weight of 1,2-cyclohexanediol diglycidyl ether, 30 parts by weight of 3,4-epoxycyclohexyl methacrylate, 30 parts by weight of organically modified zirconium dioxide and 1 part by weight of 3-glycidyloxypropyltrimethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component A.

[0085] S2: 38 parts by weight of 2-naphthylmethyl 2-acrylate, 35 parts by weight of organically modified zirconium dioxide, 12 parts by weight of isophoronediamine, 2 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 5 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0086] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0087] Embodiment 10:

[0088] S1: 60 parts by weight of 1,2-cyclohexanediol diglycidyl ether, 30 parts by weight of 4-hydroxybutyl acrylate glycidyl ether, 30 parts by weight of 4-hydroxybutyl acrylate glycidyl ether, 30 parts by weight of organically modified zirconium dioxide and 1 part by weight of 3-glycidyloxypropyltrimethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500rpm, and the stirring time is 4h to obtain component A.

[0089] S2: 38 parts by weight of 2-naphthylmethyl 2-acrylate, 35 parts by weight of organically modified zirconium dioxide, 12 parts by weight of isophoronediamine, 2 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 5 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0090] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0091] Embodiment 11:

[0092] S1: 60 parts by weight of 1,2-cyclohexanediol diglycidyl ether, 30 parts by weight of 4-hydroxybutyl acrylate glycidyl ether, 30 parts by weight of organically modified zirconium dioxide and 1 part by weight of 3-glycidyloxypropyltrimethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component A.

[0093] S2: 38 parts by weight of 2-phenoxyethyl methacrylate, 35 parts by weight of organically modified zirconium dioxide, 12 parts by weight of isophoronediamine, 2 parts by weight of diphenyl (2,4,6-triformyl) phosphine oxide and 5 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0094] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0095] Comparative Example 1:

[0096] S1: 40 parts by weight of bis(7-oxabicyclo[4.1.0]3-heptylmethyl)adipate, 30 parts by weight of ethyl acrylate, 25 parts by weight of organically modified zirconium dioxide and 1 part by weight of y-aminopropyltriethoxysilane were put into a reaction kettle and stirred. The temperature was controlled at about 40°C, the stirring speed was 1500 rpm, and the stirring time was 4 hours to obtain component A.

[0097] S2: 25 parts by weight of bisetherfluorene acrylate, 35 parts by weight of organically modified zirconium dioxide, 12 parts by weight of isophoronediamine, 2 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 5 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0098] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0099] Comparative Example 2:

[0100] S1: 60 parts by weight of 1,2-cyclohexanediol diglycidyl ether, 30 parts by weight of 2-cyclohexyl methyl acrylate, 30 parts by weight of 4-hydroxybutyl acrylate glycidyl ether, 30 parts by weight of organically modified zirconium dioxide and 1 part by weight of 3-glycidyloxypropyltrimethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component A.

[0101] S2: 38 parts by weight of 2-naphthylmethyl 2-acrylate, 35 parts by weight of organically modified zirconium dioxide, 12 parts by weight of isophoronediamine, 2 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 5 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0102] Comparative Example 3:

[0103] S1: 60 parts by weight of 1,2-cyclohexanediol diglycidyl ether, 30 parts by weight of 4-hydroxybutyl acrylate glycidyl ether, 30 parts by weight of 4-hydroxybutyl acrylate glycidyl ether, 30 parts by weight of organically modified zirconium dioxide and 1 part by weight of n-octyltriethoxysilane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500rpm, and the stirring time is 4h to obtain component A.

[0104] S2: 38 parts by weight of 2-naphthylmethyl 2-acrylate, 35 parts by weight of organically modified zirconium dioxide, 12 parts by weight of isophoronediamine, 2 parts by weight of diphenyl(2,4,6-triformyl)phosphine oxide and 5 parts by weight of polyether-modified polydimethylsiloxane are put into a reaction kettle and stirred. The temperature is controlled at about 40°C, the stirring speed is 1500 rpm, and the stirring time is 4 hours to obtain component B.

[0105] Product preparation: Add component A and component B in a ratio of 1:1 into a reactor and stir. Control the temperature at 20°C and stir at a speed of 1500 rpm for 5 minutes to obtain a composition.

[0106] Comparative Example 4:

[0107] 60 parts by weight of 4,5-epoxytetrahydrophthalic acid diglycidyl ester, 25 parts by weight of 3,4-epoxycyclohexyl methacrylate, 15 parts by weight of 4-biphenylmethanol acrylate, 2 parts by weight of 3-glycidyloxypropyltrimethoxysilane, 40 parts by weight of 4-biphenylmethanol acrylate, 60 parts by weight of organically modified zirconium dioxide, 5 parts by weight of isophoronediamine, 5 parts by weight of diphenyl (2,4,6-triformyl) phosphine oxide and 8 parts by weight of polyether-modified polydimethylsiloxane were put into a reaction kettle and stirred. The temperature was controlled at about 40° C., the stirring speed was 1500 rpm, and the stirring time was 4 hours to obtain a composition.

[0108] Comparative Example 5:

[0109] 55 parts by weight of bisphenol A difunctional epoxy acrylate, 35 parts by weight of 2-hydroxyethyl methacrylate, 35 parts by weight of isobutyl acrylate, 60 parts by weight of organically modified titanium dioxide, 8 parts by weight of isophorone diamine, 3.5 parts by weight of diphenyl (2,4,6-triformyl) phosphine oxide, 3 parts by weight of polyether modified polydimethylsiloxane and 1 part by weight of y-aminopropyltriethoxysilane were put into a reaction kettle and stirred. The temperature was controlled at about 40° C., the stirring speed was 1500 rpm, and the stirring time was 4 hours to obtain a composition.

[0110] Performance testing:

[0111] For the compositions prepared in Examples 1-11 and Comparative Examples 1-5, the viscosity at 25°C was tested using a viscometer; the compositions prepared in Examples 1-11 and Comparative Examples 1-5 were coated on a substrate, UV cured for 6 seconds, and thermally cured for 1.5 hours to form a 10 μm thick film; the composition prepared in Example 3 was thermally cured and UV cured at the same time to form a 10 μm thick film (denoted as D6) to test the light transmittance; the shear strength of the 10 μm thick film formed by Examples 1-11 and Comparative Examples 1-5 after UV curing was tested using an AGS-X universal testing machine, and the shear strength was tested again after boiling in water at 150°C for 60 minutes. The test results are shown in Table 1 below:

[0112] Table 1

[0113]

[0114]

[0115] As can be seen from the above table, the high refractive index optical adhesive prepared by the present invention using epoxy resin, acrylates and acrylates containing specific reactive groups, metal oxide nanoparticles, photoinitiators and additives has a viscosity of 500cps-1000cps at room temperature and can be used for coating, spraying, spin coating and other processes. In addition, the technical solution of the present application combines epoxy resin with acrylates containing specific reactive groups, and is equally divided into two components AB with a curing agent to avoid the cross-linking and curing reaction of epoxy resin at room temperature and improve the overall storage stability of the optical adhesive; at the same time, it can be seen from Examples 1-11 and D5 that the AB component is combined with the technical means of UV curing first and then thermal curing, and the obtained adhesive layer is resistant to high temperature and has good water and oxygen barrier properties. Due to the presence of acrylates with reactive functional groups in component A, the degree of cross-linking with epoxy resin during UV curing is increased. After the thermal curing is complete, the curing cross-linking density of the resin component in the overall component is relatively high, thereby improving the comprehensive properties of the refractive index, light transmittance, shear strength, etc. after the photocurable composition is cured to form an optical film. It is a high refractive index optical adhesive with a stable system and excellent performance after curing into a film.

[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-fold double-curing adhesive, characterized in that: Contains the following components in parts by weight: Component A comprises: 40-80 parts of epoxy resin, 10-40 parts of first acrylate, and 15-30 parts of first inorganic filler; and component B, which includes: 20-50 parts of a second acrylate, 30-80 parts of a second inorganic filler, and 5-20 parts of a curing agent; in: The first acrylate comprises at least a (meth)acrylate monomer containing one or more reactive groups, wherein the reactive groups are selected from hydroxyl, epoxy or carboxyl groups; The second acrylic acid ester is selected from any one or more combinations of (meth)acrylic acid aryl ester monomers, (meth)acrylic acid alkyl ester monomers or (meth)acrylic acid alkyl ether ester monomers.

2. The high-fold double-curing adhesive according to claim 1, characterized in that: When the reactive group is an epoxy group, the skeleton of the first acrylate is an alkyl group, an alkyl ether group or an aromatic group having 1-2 benzene ring groups, and at least one end of the first acrylate has one or more glycidyl ether groups or epoxy cyclohexyl groups.

3. The high-fold double-curing adhesive according to claim 2, characterized in that: The alkyl group is C1-C 20 Alkyl, C3-C 20 Heterocycloalkyl or C1-C 20 alkyl; The aryl group is C6-C 30 Aryl.

4. The high-fold double-curing adhesive according to claim 3, characterized in that: The second acrylate includes at least a (meth)acrylate aryl ester containing two or more substituted or unsubstituted phenyl groups.

5. The high-fold double-curing adhesive according to claim 1, characterized in that: The epoxy resin is selected from any one or more combinations of bisphenol A epoxy resin, bisphenol S epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, novolac epoxy resin or epoxy glycidyl ester.

6. The high-fold double-curing adhesive according to claim 1, characterized in that: The first inorganic filler is selected from one or more combinations of organically modified or unmodified metal oxides and silicon dioxide; The second inorganic filler is selected from one or more combinations of organically modified or unmodified metal oxides and silicon dioxide.

7. The high-fold dual-curing adhesive according to claim 1, characterized in that: The curing agent includes a photocuring agent and a thermal curing agent.

8. The high-flex dual-curing adhesive according to any one of claims 1 to 7, characterized in that: The high-flex dual-curing adhesive further comprises a silane coupling agent, and the silane coupling agent contains at least one functional group of a hydroxyl group, an epoxy group or an amino group.

9. A method for preparing a high-flex dual-curing adhesive according to any one of claims 1 to 8, characterized in that: The steps include: S1: adding epoxy resin, first acrylate and first inorganic filler into a reaction kettle and stirring to obtain component A; S2: adding the second acrylate, the second inorganic filler and the curing agent into a reaction kettle and stirring to obtain component B; S3: Add component A and component B into a reaction kettle at a weight ratio of (1-1.5):1 and stir to obtain a composition.

10. An application of the high-flex dual-curing adhesive according to any one of claims 1 to 8, characterized in that: The high-refractive dual-curing adhesive is subjected to a pre-curing reaction under ultraviolet light irradiation, and then cured at a temperature of 100-130° C. to obtain an adhesive layer.

Citation Information

Cited By

  • Polythioether polymer, high-refractive-index OCA (Optical Clear Adhesive) containing same as well as preparation method and application of high-refractive-index OCA

    CN120842575A